The Nairobi Summit and Reproductive Justice: Unmet Needs for People with Infertility - Dierickx, Susan (Am J Trop Med Hyg, 2021)
The Nairobi Summit, held in November 2019 and convened by the United Nations Fund for Population Activities, claims to have represented “all nations and peoples, and all segments” of society during its high-level conference. The overall aim of the summit was to mobilize political will and financial commitments that are urgently needed to “finally and fully” implement the 1994 International Conference on Population and Development (ICPD) Program of Action. Despite the recommendation by ICPD to incorporate infertility care in reproductive health services, the new Nairobi Statement largely neglects the topic of infertility. This is particularly troublesome as infertility is a global health problem affecting between 52.6 and 72.4 million couples worldwide, with a high prevalence in low- and middle-income settings. For many people around the world, infertility constitutes an emotional, social, and financial burden, yet appropriate services directed toward preventing and addressing infertility are often inaccessible, unaffordable, or nonexistent. With the impetus of a wider reproductive justice community, we call for the integration of infertility into global reproductive health research and practice, urging policy makers, practitioners, researchers, activists, and funders worldwide to bring focused attention to addressing challenges posed by a lack of safe, effective, and dignified fertility management among those in need.